Computational intelligence techniques with application to crude oil price projection: a literature survey from 2001–2012 - Haruna, Chiroma; Sameem, Abdul-kareem; Abubakar, Adamu; Joda, Mohammed (Czech Technical University in Prague, 2013)
This paper is an attempt to survey the applications of computational intelligence techniques for predicting crude oil prices over a period of ten years. The purpose of this research is to provide an exhaustive overview of the existing literature which may assist prospective researchers. The reviewed literature covers a spectrum of publications on the proposed model, source of experimental data, period of data collection, year of publication and contributors. The overall trend of the publications in this area of research issued within the last decade is also addressed. The existing body of research has been analyzed and new research directions have been outlined that have been previously ignored. It is expected that researchers across the globe may thus be encouraged to re–direct their attention and resources in order to keep on searching for an optimum solution